SAGO BARUK PALM (Arenga microcarpha Becc) AS A SUPERIOR LOCAL FOOD SOURCE AND SOIL CONSERVATION PLANT AT SANGIHE ISLAND REGENCY - Marianus, Marianus; Ashari, Sumeru; Rahardjo, Bambang Tri; Polii-Mandang, Bobby (AGRIVITA, Journal of Agricultural Science, 2012)
Sagu Baruk Palm (Arenga microcarpha) is an endemic plant and producing carbohydrates as main source of local food to the people in Sangihe Island . The aim of this study is to analyze the production of  the sago and to analyze its the chemical composition and nutritional value. The research was conducted from October 2010 to June 2011 at Gunung Village Tabukan Tengah Regency Sangihe district Island. The village is spread from the coast up to the top of the hill with an altitude of ± 600 meters above sea level. The data analysis techniques in this research is descriptive analysis, F test, ANOVA.The results showed that the production of Sagu Baruk Palm at the third height position for the stem lenght 9.7-11m and stem diameter 14.3-15.7cm obtain wet sago flour 44-44.3kg and the stem rendemen from 21.3% to 22.3%, statistically only stem weight and pith weight has a significant different. The highest stem weight obtained at the bottom position, the highest pith weight obtain at the top position, and for the higest stem rendemen obtain at the top position . The chemical composition were significant differences in levels of protein, calcium, iron, magnesium, and pH at the three height positions.Key words: Superior local food sources, stem rendemen, production, sagu baruk palm.